ANALISIS PEMANFAATAN HUTAN KOTA DI KOTA KOTAMOBAGU - Paransi, Sundari E.; ., Sangkertadi; Wuisang, Cynthia E. V. (MEDIA MATRASAIN, 2021)
The urban forest is one type of urban green open space, which is an area in which there are dense and compact trees and is an important conservation in the urban environment. O2, the center of habitat for flora and fauna of liars, provider of urban aesthetics, etc. There are also Bonawang Urban Forests in Kotamobagu City – the benefits identified using Soil Surface Temperature were analyzed using ArcGIS, Air Quality Calculations, and the calculation of the minimum area of the urban forest. With the results that there are still areas with high temperatures of 29-30˚C, the IKU in urban forests is classified as moderate, the minimum area of urban forests for Kotamobagu City is 1,105.62 m2, around the industrial area because there is a Bulog factory 600 m from the City Forest. Bonawang, is still not prominent, and some people have not felt the benefits of urban forests from their homes.